Neuro-immune interactions in obesity - Pirzgalska, Roksana Maria (2018)
For the past few decades, obesity has emerged as one of the major complex diseases affecting human populations. Despite recent breakthroughs in ameliorating some of the complications associated with this disease, there are still no effective therapies against obesity To understand obesity one must know how the adipose tissue (AT) is regulated in normal and affected conditions. Our knowledge on AT biology has grown significantly in the last few years. This knowledge has resulted in a clearer picture of how obesity shapes the AT. In this regard, we have decided to focus our work on one important aspect of AT biology: its neuro-immune regulation. More specifically, we set out to understand if signals originating from the sympathetic nervous system (SNS) can modulate the adipose mass, and if such signaling may be regulated at the immunological level. Here we show that sympathetic nerve bundles target the subcutaneous white AT (WAT). Furthermore, we demonstrate that the sympathetic axons in the WAT mediate the lipolytic response to leptin. Importantly, local ablation of the SNS in WAT resulted in decreased leptin activity and blunted lipolysis. Conversely, by using optogenetics to selectively activate these sympathetic bundles, we observed a local release of the neurotransmitter norepinephrine (NE) and subsequent fat loss. Our data provide evidence supporting that sympathetic axons in the AT are both necessary and sufficient for leptin-driven lipolysis in WAT. Obesity has long been associated with low-grade inflammation in peripheral tissues and in the central nervous system (CNS). We have observed that obesity-associated low-grade inflammation also occurs in the SNS. By using multiphoton microscopy tools, we demonstrate that sympathetic axons in WAT are populated by a discrete population of macrophages with cellular characteristics different from those of the macrophages in the surrounding AT. Such Sympathetic-neuron Associated Macrophages (SAM) exhibit profuse dendritiform processes, which dynamically extend and retract over time. On the other hand, AT macrophages (ATMs) were smaller, round and had a substantially different cellular displacement. Our study demonstrates that obesity-induced inflammation of the AT preferentially affects the sympathetic nerve fibers targeting the WAT and is closely associated with the accumulation of SAMs. Furthermore, we also observed that obesity drove the up-regulation of pro-inflammatory profiles in both SAMs and ATMs. We provide some insight into the possible mechanism that may link macrophages in the AT to the neurotransmitter NE. Our results suggest that SAMs possess the machinery to incorporate NE (via the Norepinephrine Transporter SLC6A2) and to catabolize it (via the enzyme Monoamine Oxidase-A). Of note, this machinery was not present in any other macrophage population we studied. In this regard, the deletion of SLC6A2 in the hematopoietic compartment (by bone marrow transfer from SLC6A2- KO mice into genetically obese ob/ob mice), improved thermogenic capacities and fat oxidation in this mouse model of obesity. Overall, our results demonstrate the functional significance of the neuro-immune interface for the regulation of the adipose tissue during obesity.